Training on the Use of Google Classroom-Based E-Learning at MIS Guppi Teppo - Emha Dziaul Haq; Sri Adiningsih; Nurul Riska; Samsul Ridah (Jurnal Pengabdian IPTEK, 2026)
Learning in the digital age requires teachers to not only master the subject matter, but also be able to deliver creative, interactive, and in-depth learning based on digital technology. To address these issues and challenges, the author provides a solution in the form of e-learning training activities, namely training in the use of Google Classroom. The purpose of this activity is to improve teachers' digital competence in designing and implementing digital-based learning. There were 12 participants, consisting of teachers and the principal of MIS Guppi Teppo, Banggae District, Majene Regency. The implementation methods included material delivery, demonstrations, hands-on practice, mentoring, and activity evaluation. The training results showed that this activity made a significant contribution to improving teachers' understanding and competence in utilizing digital media to support digitization in education. This was evident from the participants' pretest and posttest results, which showed an increase from 63.1 to 81.8.